METHOD OF DEFENITION OF TRIBOLOGICAL CHARACTERISTICS OF ANTIFRICTION SYSTEMS - Кіндрачук, М. В.; Кульгавий, Е. А.; Шевченко, О. Л.; Данілов, А. П. (Science-based technologies, 2009)
The method of definition of characteristics of deterioration in the form of statistical models is onsidered. Application of the statistical analysis is connected with internal structure of process of deterioration, the example of constructions of the characteristic in the form of a polynom of the second degree is resulted.